La actividad lúdica como estrategis pedagògica para fortalecer el aprendizaje motor - Chugchilan Guamangallo, Luis Miguel (2017)
The research was carried out to demonstrate how the leisure activities can improve the motor learning of the students belonging to Escuela de Educación Básica Lic. "Jaime Andrade Fabara", at the moment of exercising. In order to transmit to the children the importance that motor development has the benefits that will be obtained, also to be applied through the game. The field methodology research was used because it was carried out in the place of the facts, the present study was carried out in a quantitative way through surveys, thus through the information provided in this document it was found that leisure activities improve motor activities. For this reason, researchers seek to design strategies to improve their motor learning in the students and also to strengthen in each of them. That is why, the teacher should teach their students the different recreational activities that consist in the area of Physical Education, since the game is an ideal medium for learning and developing their different skills and abilities. With the implementation of leisure activities the results will be favorable, the importance of the game in the motor development of the student, evidences the need to apply it in the classroom, especially at an early age, is of vital importance because it favors in individuals self-confidence, autonomy and strength the personality, thus becoming one of the recreational and educational activities, for their stimulation, it is necessary teachers strengthens spaces and suitable times to share, so that the entire educational community can participate actively in daily activities, distraction and apathy before the development.